(untitled) (مجلة وقف في دراسات الاوقاف, 2026)
The author was born in Damascus in 1940 AD. He obtained a Bachelor of Commerce in 1962 from the University of Damascus and a PhD in Economics in 1975 from the University of Utah in America, named: The economics of money and development. He has more than 15 books in Arabic and English, and more than 60 articles in Arabic and English, as well as contributions to conferences and seminars. The book was published by the Dar Aftekr AL Muaser in Lebanon, and Dar al-Fikr in Damascus. Syria, year of publication: 1421 AH-2000 CE in one volume, 329 pages, and it includes four sections and twenty-three chapters. It is one of the encyclopedic literature; Where it included most of the endowment topics, sayings of jurisprudence and Fiqhi schools. He compared and tended to some opinions. He supported his opinion with Legal and mental evidences. In the first chapter, he spoke about the development of the idea of waqf and its growth in ancient societies and in the Islamic era and how it spread to Europe and then America, and how its legal organizations developed. Also, he talked about the appearance of Family endowment in Islam, which Western laws did not know it until the second half of the twentieth century. He considered Family Endowment, an Islamic industry.